APLIKASI PERAMALAN HARGA PENUTUPAN DAN PERKIRAAN ARAH PADA ONLINE FOREX - Trisdiyanto, Stevanndy; Lubis, Chairisni; Tumbelaka, Bobby (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
This application uses artificial neural networks that generate value of the closing price on the day and uses three indicators of technical analysis to help estimate the movement of trading foreign currency price. The data used for input values is from price movements that occurred the previous day. Closing price refers to the combination of the opening price, highest price, lowest price, closing price and volume. After getting the value of the output in the form of today's closing price, then the next will be combined with the results of the estimated direction of movement of currency rates obtained by using three indicators : indicators Bollinger Bands, indicators DeMarker and indicators Moving Average Convergence / Divergence (MACD). The test results showed that the percentage of success is good for 85.22% and get a profit 9,448.